Chronic demyelinating polyneuropathy associated with eosinophilia-myalgia syndrome. - Freimer, M L (1992)
Eosinophilia-myalgia syndrome (EMS) is a newly described syndrome associated with use of L-tryptophan. A neuropathy with features of axonal degeneration has also been described in conjunction with EMS. Demyelinating polyneuropathy is not a well recognised association of the syndrome. The two patients with EMS reported presented with profound weakness and sensory loss and were found to have clinical, electrophysiological and pathological evidence of a chronic demyelinating polyneuropathy. The concurrence of this neuropathy with EMS, as well as several other features of their illness, is suggestive of an immune mediated mechanism in the pathophysiology of EMS.